Integrasi Psikologi Pendidikan dan Analisis Kesalahan Bahasa dalam Peningkatan Kualitas Pembelajaran - Tobondo, Yuyun Alfasius; Tondowala, Sulvia Fery Hanry (Interdisciplinary Journal (IDe), 2024)
This study aims to explore how the integration of educational psychology and error analysis in language can improve the quality of learning. Through a systematic literature review (SLR) approach, this research examines various relevant studies to identify effective methods for enhancing students' learning interest and reducing language errors. The results show that game-based learning design can increase students' learning interest by 330%, and the implementation of an independent curriculum has a positive impact on producing skilled and creative generations. The empowerment of pedagogical competence based on reflective capabilities and training in phenomenon-based learning methods have also proven effective in improving the quality of learning interactions. These findings emphasize the importance of teacher training in information technology and innovative teaching methodologies, as well as the development of information systems that support better educational administration. The integration of educational psychology and language error analysis not only improves student learning outcomes but also prepares them to compete globally. Further research is needed to optimize the use of technology and family environmental factors in supporting students' learning processes.